Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific - White, William T.; Last, Peter R.; Stevens, John D. (Zootaxa, 2007)
A new species of Mandarin dogfish, Cirrhigaleus australis n. sp., is described based on specimens from southeastern Australia. Australian populations were previously considered to be conspecific with Cirrhigaleus barbifer from the western North Pacific and Indonesia, but recent investigations revealed that the two forms differ in morphology and in the structure of the CO1 gene. Cirrhigaleus australis has a smaller eye, shorter dorsal-caudal space, and smaller pectoral fins and dorsal fins and spines. These species are clearly separable from the only other congener, C. asper, and all other members of the family Squalidae, by the possession of a greatly produced barbel on their anterior nasal flap. The new species occurs in temperate waters of eastern Australia, and possibly New Zealand.